Production of yellow passion fruit under different planting densities - Júnior, Valter Carvalho de Andrade; Neto, Sebastião Elviro de Araújo; Rufini, José Carlos Moraes; Ramos, José Darlan (Pesquisa Agropecuaria Brasileira, 2003)
The density of plants in cultivations of yellow passion fruits is important, because it provides larger profitability in smaller areas. The objective of this research was to evaluate the effect of different planting densities on production, quality of fruit and profitability of yellow passion fruit. The experiment was installed in a commercial orchard in Sant'ana Farm, district of São Tiago, MG, Brazil. The experimental design was in randomized blocks with five treatments and four replications. The treatments were different planting densities: T1, 1.0 m (3,330 plants/ha); T2, 1.5 m (2,220 plants/ha); T3, 2.0 m (1,660 plants/ha); T4, 3.0 m (1,100 plants/ha) and T5, 4.0 m (830 plants/ha). The distance between the lines was 3.0 m to all the treatments. Each plot was 12 m long and 3.0 m wide (36 m2). The planting was accomplished in October of 2001. The harvest began in April extending to August of 2002. The largest productivity was 11.9 ton/ha at a density of 1,841 plants/ha. Planting density did not change the quality of the fruits. The largest economical efficiency was reached under the density of 1,340 plants/ha, with a profitability of R 1,321.92/ha.